Design, Characterization, and Lead Selection of Therapeutic miRNAs Targeting Huntingtin for Development of Gene Therapy for Huntington's Disease - Jana Miniarikova; Ilaria Zanella; Angelina Huseinovic; Tom van der Zon; Evelyn Hanemaaijer; Raygene Martier; Annemart Koornneef; Amber L Southwell; Michael R Hayden; Sander J van Deventer; Harald Petry; Pavlina Konstantinova (Elsevier, 2016)
Huntington's disease (HD) is a neurodegenerative disorder caused by accumulation of CAG expansions in the huntingtin (HTT) gene. Hence, decreasing the expression of mutated HTT (mtHTT) is the most upstream approach for treatment of HD. We have developed HTT gene-silencing approaches based on expression cassette-optimized artificial miRNAs (miHTTs). In the first approach, total silencing of wild-type and mtHTT was achieved by targeting exon 1. In the second approach, allele-specific silencing was induced by targeting the heterozygous single-nucleotide polymorphism (SNP) rs362331 in exon 50 or rs362307 in exon 67 linked to mtHTT. The miHTT expression cassette was optimized by embedding anti-HTT target sequences in ten pri-miRNA scaffolds and their HTT knockdown efficacy, allele selectivity, passenger strand activity, and processing patterns were analyzed in vitro. Furthermore, three scaffolds expressing miH12 targeting exon 1 were incorporated in an adeno-associated viral serotype 5 (AAV5) vector and their HTT knock-down efficiency and pre-miHTT processing were compared in the humanized transgenic Hu128/21 HD mouse model. Our data demonstrate strong allele-selective silencing of mtHTT by miSNP50 targeting rs362331 and total HTT silencing by miH12 both in vitro and in vivo. Ultimately, we show that HTT knock-down efficiency and guide strand processing can be enhanced by using different cellular pri-miRNA scaffolds.